Biodegradation Behavior of PVA/Corn Starch Blend Films under the Influence of α-amylase Solution Immersion, Soil Burial and Water immersion - Jaafar, Harith; Majeed, Kawakib; Kamil, Mohanad (Iraqi Journal of Science, 2023)
The objective of this work is to study the influence of α-amylase enzymatic solution immersion, soil burial and water immersion on the biodegradability behavior of polyvinyl alcohol (PVA) /Corn Starch (CS) blend films Polyvinyl alcohol (PVA) /Corn Starch (CS) blend films were prepared by solution casting method with different weight percentages of PVA(0%,10%,30%,50%,70% and 90%) . The biodegradability of the films has been investigated by determination the weight loss of the tested films. It was noticed that the films containing corn starch were highly biodegraded under above influences. The weight loss of the tested films decreased with increasing PVA content and increased with immersion time in enzymatic solution and water and soil burial time